Higher Education Financing in a Time of International Crisis: The Australian Exception - Chapman, Bruce (International Higher Education, 2024)
The student loan systems of most countries have recently been in crisis. Many former students are confronted with insurmountable repayment difficulties, which for many results in default and can ruin their personal financial future. The situation became very visible during the COVID-19 pandemic. It exposed the key role of insurance against repayment hardship and default, essential to income-contingent student loan systems (ICL), such as that used in Australia.